Sarcoidosis or Tuberculosis? Detecting Mycobacterium tuberculosis Complex DNA in Sarcoidosis Granulomas - Shamaei, Masoud; Javadi, Alireza; Sadr, Makan; Pourabdollah, Mihan (Current Respiratory Medicine Reviews, 2018)
Background: Sarcoidosis is a granulomatous inflammatory disorder with unknown etiology and its relation with Mycobacterium tuberculosis (M. tuberculosis) has been debated for years. In this study, we have investigated the presence of mycobacterial DNA in sarcoidosis tissue samples. Methods: Formalin-Fixed Paraffin-Embedded (FFPE) tissues of 33 patients with sarcoidosis were analyzed for the presence of mycobacterial DNA. Genomic DNA extraction was done by QIAamp DNA FFPE Tissue Kit. Polymerase chain reaction using insertion element IS6110 of M. tuberculosis complex (MTC) was applied by commercial kits (GeneProof) for all individuals. The results were compared with 27 patients with tuberculosis and 5 other patients associated with granulomatous disease of the lung. All cases had confirmed granulomatous inflammation in their histopathological examination. Results: In this study, the IS6110 repetitive DNA element of (MTC) was not detected in any of the tissue samples from the patients with sarcoidosis. Of the 33 sarcoidosis patients, 30 (90.1%) had negative results for IS6110 and despite the repeated attempts of DNA extraction for three patients (9.1%), strong inhibitor made constant negative outcomes. In contrast, in patients with tuberculosis, 22 (81.5%) had positive results, three had (11.1%) negative results and 2 patients (7.4%) showed negative results with strong inhibitor. IS6110 was not found in any of the control group patients. Discussion: This study does not support the presence of M. tuberculosis in tissues of patients with sarcoidosis as a microbial pathogen or trigger of the immune response. Due to difficulties in diagnosis of sarcoidosis and different methods for diagnosis of M. tuberculosis, the impact of M. tuberculosis as a possible aetiological agent in sarcoidosis has been the point of debate.
Keywords: sarcoidosis